PKM GERMAS di Sekolah Dasar Negeri 2 Medahan, Kecamatan Blahbatuh, Kabupaten Gianyar - Ni Putu Widya Astuti; Nyoman Suarjana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
The GERMAS (Gerakan Masyarakat Hidup Sehat or healthy-live society program)  is a government program as an effort to increase the level of public health. Healthy living behavior should be instilled as early as possible. The implementation priority of GERMAS is for the elementary school. Medahan 2 Elementary School is one of the elementary schools in Medahan Village, Blahbatuh District, Gianyar Regency. Students and teachers at Medahan 2 Elementary School share common problems that are not yet aware of the GERMAS and PHBS programs. In addition, the lack of supporting facilities that are feasible for PHBS implementation is an obstacle in the implementation of the GERMAS program, especially on environmental cleanliness and the use of coloring agents in food. It is expected that after socialization and training, there will be an increased knowledge about the GERMAS program, improved implementation of physical activities, elevated consumption of natural dyes and environmentally hygiene foods, increased knowledge of PHBS, improved knowledge on the proper hand washing method, and improved quality of supporting facilities for school environment cleanliness. The results of this dedication showed an increase in PHBS facilities, especially hand washing places for elementary school students in  Medahan 2 Elementary School. Educational activities on GERMAS, especially environmental hygiene and food without harmful chemicals increased student knowledge by 92.3%. The hand washing method was increased by 89.5% at the end of GERMAS program.